A catalog of the Lampyridae (Coleoptera) of the West Indies - Keller, Oliver; Branham, Marc A. (Zootaxa, 2021)
The West Indies represents one of the world’s hotspots for beetles in the family Lampyridae and includes many endemic taxa. Nine out of 19 genera and 181 out of 186 species of the currently described firefly taxa present in the West Indies are endemic to the region. The objective of this catalog and bibliography is to generate an exhaustive list of firefly taxa present in the West Indies. A short discussion of previous efforts to catalog this fauna is presented, and all published distribution data is herein synthesized. This catalog serves as a starting point for systematic and taxonomic research on the fireflies of this region and provides a full bibliography for each species. The following species were deemed subspecific and unavailable: Callopisma rufa var. humeralis E. Olivier, Lucidota fulvotincta var. flavicollis Mutchler, and Robopus magnus var. turquino (Mutchler).